Benefits of Museums as Media and Learning Resources in Social Studies Subjects for Junior High School Students - Sihole, Beresman; Ambarita, Ratoga; Panjaitan, Friska; Napitu, Ulung; Saragih, Hisarma (Lembaga Penelitian dan Pendidikan Mandala, 2023)
This study aims to examine the existence of the museum as a medium and source of learning for students, especially in junior high school. The author chose the museum as the object of study which is a medium and source of learning for students, namely because the museum has several functions such as: 1. Collection and safeguarding of natural and cultural heritage, 2. Documentation and scientific research, 3. Conservation and preservation and 4. Dissemination. and the distribution of knowledge to the public. Museums should provide various accesses for visitors so that they can have the opportunity to use facilities and services, research and study collections, including consultation with museum staff. The conclusion of this study is that the existence of museums in the world of education is so needed, including in learning Social Sciences at the Elementary School level to the Upper Advanced Level. In the museum they can observe the relics of the past directly. The learning process can also be carried out by visitors who are not from the education community. Visitors to the museum are also able to increase their mental and intellectual property to know the past of an ethnic or community group. In museums, collection research can also be done, which can provide opportunities to produce new findings. This research is useful to arouse students' interest in knowing the past through observations of historical objects. The results of the study show that museums can motivate students and make it easy for students in the social studies learning process. The research method used in this paper is a qualitative research method of literature study. With the qualitative method of literature study, the author first collects books from the library. Researchers also seek information about the museum by conducting a library study, namely making direct visits to the library. In addition to library studies, researchers also seek and collect sources by utilizing digital technology. From the results of the research and discussion it can be concluded that the use of the Huta Bolon Museum as a source and media for social studies learning for junior high school students in Samosir Regency has a pretty good impact and provides enthusiasm for students in participating in the learning process about historical objects. The Huta Bolon Museum which has various collections in the form of statues (Tunggal Panaluan, , Boras Pati, Pangulu Balang), Buku Lak-lak, war tools (Busur and piso), tools used at home (Panituan, Hurhuran , Gampil, Sondi, Piso Halasar, Sikkop), gambling game tools (Dadu Guling and Janggar-janggar etc). Utilization of the Museum Huta Bolon Museum as a source and media for learning social studies which is visual in nature in the form of a collection of museum objects is a source and media for learning history that is representative to add insight and knowledge about events in the past